Kajian Kualitas Air Sungai Lae Renun Untuk Kesesuian Budidaya Ikan Jurung (Tor Tambra) di Desa Sumbul Kabupaten Dairi Sumatera Utara - Lora Luita Anjelina; Hasan Sitorus; Indra Lesmana (AQUACOASTMARINE, 2018)
The water quality of River Lae Renun for aquaculture is based to the quality standard of PP. No. 82 year 2001 with Storet Method and Research Center and Development of Bogor Freshwater Aquaculture. The research was conducted in May - June 2017 at Lae Renun River. The method used is Purposive Sampling method. Sampling was done on every 3 stations. Physical,chemical and Biological parameters of Lae Renun River waters based on Research and Development Center of Bogor Freshwater Culture classified in the category of Light Polluted, where the waters of Lae Renun River is still suitable for aquaculture.Keywords :Water Quality, Jurung Fish Culture, River Lae Renun